Protein phosphorylation analysis by electrospray mass spectrometry : a guide to concepts and practice - Lehmann, Wolf D. (Royal Society of Chemistry, 2010)
Protein phosphorylation analysis is a central theme in current analytical biochemistry, cell biology and systems biology. Due to its versatility, specificity and sensitivity, mass spectrometry has developed into a key technology in this field. A set of minor and major instrumental innovations mean that mass spectrometers now exhibit a level of performance, a stability of operation, a relative ease of use, and productivity, which would once have been hard to imagine. This book guides the reader through this prolific field by presenting a collection of personal views and selected examples which.